Refactoring Code Clone Detection - Othman, Zhala Sarkawt; Kaya, Mehmet (Ieee, 2019)
Refactoring duplicate code is an important issue and is one of the most important smells in software maintenance. There is an important relationship between clones and code quality. Most programmers use clones because they are cheaper and faster than typing the program code. A cloning code is created by copying and pasting the existing code fragments of the source code with or without slight modifications. A major part (5% to 10%) of the source code for large computer programs consists of copy codes. Since cloning is believed to reduce the possibility of software maintenance, many techniques and cloning detection tools have been recommended for this purpose. The basic goal of clone detection is to identify the clone code and replace it with a single call to the function, where the function simulates the behavior of one instance of the clone group. This research provides an overview of the refactoring IDE. The aspects of cloning and detection of cloning are explained. In the copy detection algorithm, the source code is created in XML format.
7th International Symposium on Digital Forensics and Security (ISDFS) -- JUN 10-12, 2019 -- Barcelos, PORTUGAL
Keywords: Refactoring; Code Clone; Clone Detection